Clinico-epidemiological study of cutaneous adverse drug reactions among the in-patients of dermatology department, Goa Medical College, Goa - Naik, Shubham; Pereira, Ian A.; Naik, Ravina; Zore, Jano (International Journal of Research in Dermatology, 2022)
Background: An adverse drug reaction (ADR) remains often remains underreported and leads to underestimated cause of morbidity and mortality. ADR frequently manifests as adverse cutaneous drug reactions (ACDRs) and manifestations varies from mild acneiform eruption to life threatening events like toxic epidermal necrolysis. Aim was to study clinic-epidemiological pattern of various ACDRs among inpatients in department of dermatology and study common drugs causing ACDRs and assess causality and severity. Methods: This retrospective observational study was conducted for a period of one year in department of dermatology in Goa Medical College. All patients fulfilling criteria of study were included. Results: A total of 24 patients were studied. Most common ACDR was observed in age group of 21-40 years. Stevens Johnson syndrome (SJS) (25%) was most common ACDR followed by morbilliform drug rash (20.8%). Other manifestation was DRESS (12.5%), fixed drug eruption (FDE) (12.5%) and angioedema (12.5%), acute generalized exanthematous pustulosis (AGEP) (8.33%); erythroderma (4.16%) and urticaria (4.16%). Antibiotics were commonly implicated drug category in causation of ACDRs accounting for 37.5% followed by NSAIDS (25%). Based on causality assessment, probable cases had higher incidence - 54.2% followed by possible 37.5%. All patients were considered to have severe reaction as patients required hospitalization for management of adverse reactions. Conclusions: ADRs are under-reported due to various factors and practicing doctors should be encouraged to report ACDRs in order to improve medical therapy for the benefit of healthcare workers and patients worldwide.